Refill friction stir spot welding of AlSi10Mg alloy produced by laser powder bed fusion to wrought AA7075-T6 alloy. (October 2022) - Fritsche, S.; Draper, J.; Toumpis, A.; Galloway, A.; Amancio-Filho, S.T.
Graphical abstract: Abstract: In this study, refill friction stir spot welding (RFSSW) was used to join AlSi10Mg, produced by laser powder bed fusion (LPBF), to high-strength wrought AA7075-T6 alloy. The investigation showed the best mechanical properties and integrity of the joint are achieved with medium heat input, where the optimal balance between hook height and integrity was observed. The welded additive manufactured alloy shows accentuated softening in the hook region of the thermo-mechanically affected zone. The feasibility of RFSSW for joining LPBF AlSi10Mg to high-strength wrought alloys was confirmed, showing high potential for further investigations and industrial applications.